The Gothic and the Debate on Science in Spain: Echoes of Frankenstein in «Un crimen científico», Pascual López and El árbol de la ciencia - Perojo Arronte, M. Eugenia (Cuadernos de Ilustración y Romanticismo, 2022)
This article studies Gothic motifs and tropes in José Fernández Bremón’s «Un crimen científico», Emilia Pardo Bazán’s Pascual López: autobiografía de un estudiante de medicina and Pío Baroja’s El árbol de la ciencia within the tradition of Mary Shelley’s pioneering novel Frankenstein. They are instrumental for conveying the vexed question of the modernisation of Spain through scientific progress, with approaches that range from the nuanced optimism of Fernández Bremón to the downright pessimism of Baroja. This trend is part of the wider movement for a moral, political, and cultural regeneration that characterised Spanish intellectual activity at the time. The tensions between past and present appear in the three narratives in a line of continuity and readjustment of high aesthetic and intellectual relevance.